Obeticholic Acid Modulates Serum Metabolites and Gene Signatures Characteristic of Human NASH and Attenuates Inflammation and Fibrosis Progression in Ldlr‐/‐.Leiden Mice. Issue 12 (29th October 2018) - Morrison, Martine C.; Verschuren, Lars; Salic, Kanita; Verheij, Joanne; Menke, Aswin; Wielinga, Peter Y.; Iruarrizaga‐Lejarreta, Marta; Gole, Laurent; Yu, Wei‐Miao; Turner, Scott; Caspers, Martien P.M.; Martínez‐Arranz, Ibon; et al.
Abstract : Concerns have been raised about whether preclinical models sufficiently mimic molecular disease processes observed in nonalcoholic steatohepatitis (NASH) patients, bringing into question their translational value in studies of therapeutic interventions in the process of NASH/fibrosis. We investigated the representation of molecular disease patterns characteristic for human NASH in high‐fat diet (HFD)‐fed Ldlr‐/‐.Leiden mice and studied the effects of obeticholic acid (OCA) on these disease profiles. Multiplatform serum metabolomic profiles and genome‐wide liver transcriptome from HFD‐fed Ldlr‐/‐.Leiden mice were compared with those of NASH patients. Mice were profiled at the stage of mild (24 weeks HFD) and severe (34 weeks HFD) fibrosis, and after OCA intervention (24‐34 weeks; 10 mg/kg/day). Effects of OCA were analyzed histologically, biochemically, by immunohistochemistry, using deuterated water technology ( de novo collagen formation), and by its effect on the human‐based transcriptomics and metabolomics signatures. The transcriptomics and metabolomics profile of Ldlr‐/‐.Leiden mice largely reflected the molecular signature of NASH patients. OCA modulated the expression of these molecular profiles and quenched specific proinflammatory‐profibrotic pathways. OCA attenuated specific facets of cellular inflammation in liver (F4/80‐positive cells) and reduced crown‐like structures in adipose tissue. OCA reduced de novo collagen formation and attenuated further progression of liver fibrosis, but did not reduce fibrosis below the level before intervention. Conclusion: HFD‐fed Ldlr‐/‐.Leiden mice recapitulate molecular transcriptomic and metabolomic profiles of NASH patients, and these signatures are modulated by OCA. Intervention with OCA in developing fibrosis reduces collagen deposition and de novo synthesis but does not resolve already manifest fibrosis in the period studied. These data show that human molecular signatures can be used to evaluate the translational character of preclinical models for NASH. Abstract : Gene signatures and metabolites that are characteristic for NASH patients are reflected in Ldlr‐/‐.Leiden mice, a diet‐induced model of NASH and fibrosis that recapitulates many histological, phenotypical and metabolic features of NASH patients. Treatment with OCA reduced progression of fibrosis in this model and in parallel modulated the human‐NASH‐based gene signatures and metabolites.